P-OGC42 Hiatus Hernia following Minimally Invasive Oesophagectomy - a Single Centre Experience. (16th December 2021) - Rana, Mridul; Sanga, Akshata; Mastoridis, Sotiris; Sgromo, Bruno
Abstract: Background: Hiatus hernia is an established complication following oesophagectomy, with a higher incidence when a minimally invasive approach (MIO) is undertaken. Literature reports the incidence post-MIO to be vary between 4.5% -26%. There is no clear consensus on the optimum operative management of this complication. The aim of this study was to establish the incidence of hiatus hernia post MIO (HiHO) at a single hospital site, identify predisposing factors, and evaluate subsequent surgical management of this complication. Methods: Single-center data were retrospectively analysed of MIOs conducted consecutively between May 2018 and October 2020. A minimum follow-up period of 6 months was required for inclusion. HiHO was defined by radiological confirmation. Data collected included patient demographics, comorbidities, risk factors for hiatus hernia and patient's post-operative course. Statistical analyses were performed using Fischer's exact or independent t-test as appropriate. Results: 50 patients who underwent MIO were included; mean follow up of 1.92 years. 7 (14%) presented with HiHO. There was no significant difference in age or gender between patients with and without HiHO. HiHO patients had a significantly lower BMI (95% CI 1.083-8.271; P = 0.012) and were more likely to have underlying lung conditions (P = 0.029). A higher incidence of pre-existing hiatus hernia was present among the HiHO group (43% vs 21%). Of those developing HiHO, 6 (86%) were symptomatic requiring surgical reduction with crural repair of hiatus or colopexy; 2 had a recurrence of HiHO requiring subsequent colopexy. Conclusions: This study represents the largest single centre analysis of hiatus hernia post minimally invasive oesophagectomy. Our results correlate with the literature, that there is a significant risk of hiatus hernia following minimally invasive oesophagectomy. This risk is increased among patients with pre-operative hiatus hernia, low BMI, and pre-existing lung conditions. Crural repair or colopexy are options for surgical management of HiHO. Colopexy may potentially prevent recurrence of HiHO. A larger study size and a consensus from experts in the field would be beneficial in guiding operative management of HiHO to improve patient outcomes.